ATAS NAMA ISLAM: KAJIAN PENOLAKAN HIZBUT TAHRIR INDONESIA (HTI) TERHADAP PLURALISME - Paelani Setia (UIN Sunan Kalijaga, 2021)
This study discuss the views of Hizbut Tahrir Indonesia (HTI) regarding religious pluralism. HTI as an organization that is sincere in interpreting the Qur'an literally and firmly rejects religious pluralism, which many people agree on as a concept that must be applied in Indonesia. This is a logical consequence where Indonesia is inhabited by various religions bound by a sense of unity in Pancasila and Bhinneka Tunggal Ika. For HTI, this is a failure of the state to build and maintain the unity that Islam should bind through a single power (Khilafah Islamiyah). This concept has been widely criticized by scholars based on two approaches, namely the Qur'an and sociological. Clearly, the Qur'an has acknowledged the existence of pluralism through the existence and truth of the books before the Qur'an, the acknowledgment of prophets and apostles other than the 25 people, as well as the acknowledgment of the Qur'an for the existence of other religions. HTI's rejection of pluralism was also refuted by HTI's own inconsistencies as the attitude of rejecting globalization but acting as a player of globalization, the attitude of rejecting democracy but taking advantage of the openness of freedom of opinion as a result of democracy, and the attitude of blaming the system of liberalism and secularism as the factors that give rise to deviant religious sects are purely psychological and sociological factors.